2021
DOI: 10.3390/catal11060748
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extraction of Seed Oil from Mamey Sapote (Pouteria sapota) after Viscozyme L Treatment

Abstract: In this study, aqueous enzymatic extraction (AEE) was evaluated during the process of obtaining oil from mamey sapote seed (OMSS). Viscozyme L enzyme complex was used at pH 4 and 50 °C during the optimization of the extraction process by central composite design and response surface methodology. Optimal conditions were: 3.5% (w/w) of enzyme (regarding the seed weight), 5.5 h of incubation time, 235 rpm of agitation rate, and 1:3.5 of solid-to-liquid ratio. These conditions enabled us to obtain an OMSS yield of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 93 publications
(159 reference statements)
0
7
0
Order By: Relevance
“…However, during the last decades, green extraction technologies have been positioned as the most studied methods for the recovery of bioactive compounds [42]. "Green Chemistry" methods have the advantages of reducing extraction times and energy consumption as well as the possibility of using safer solvents [43], potentiating the use of mango wastes and other vegetable extracts in industries such as food and pharmaceuticals.…”
Section: Extraction Methods Of Phenolic Compounds From Mangomentioning
confidence: 99%
“…However, during the last decades, green extraction technologies have been positioned as the most studied methods for the recovery of bioactive compounds [42]. "Green Chemistry" methods have the advantages of reducing extraction times and energy consumption as well as the possibility of using safer solvents [43], potentiating the use of mango wastes and other vegetable extracts in industries such as food and pharmaceuticals.…”
Section: Extraction Methods Of Phenolic Compounds From Mangomentioning
confidence: 99%
“…Recently, Ladole et al ( 19 ) reported that pH=5 is optimal for tomato lycopene extraction using a pectinase-cellulase enzyme mixture. Interestingly, among the enzyme cocktails tested in this work, the KTN cocktail is the only one with pectinases ( 24 , 33 , 34 ), which might account for the obtained results. Enzymes can increase the yield of carotenoids in tomato extracts because these pigments are accumulated in specialised intracellular organelles and are not readily reached by solvents ( 19 ).…”
Section: Resultsmentioning
confidence: 80%
“…A compact and intact structure with many globules and no damage to the cell walls was observed in the untreated sample. However, after the extraction treatments, the surface was observed to be porous with significant damage to the cell wall (Tacias‐Pascacio et al, 2021). Extraction of oil is affected by the degree of penetration and solubility of the organic solvent into the matrix; therefore, the formation of pores observed after soxhlet extraction may be generated by the entry of hexane (Hu et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Mango is one of the notable varieties of tropical fruit recognized worldwide for its pleasant taste, aroma, and nutritional profile (Torres- Le'on et al, 2016). The area under mango cultivation in India has been reported to be around 2.26 million acres, which is 40% of the entire area under fruit cultivation in India (National Mango Database, 2021).…”
Section: Introductionmentioning
confidence: 99%